Strengthening the natural base at elongation of artificial runway at Danylo Halytskyi international airport «Lviv» - Hameliak, I. P.; Nikolaychuk, A. V.; Zhurba, H. V. (Science and Transport Progress, 2012)
In the article, the main requirements and an example of calculation of strengthening the weak base by geosynthetic materials for reconstruction of Lviv airport within the framework of preparation to Euro-2012 are displayed. The requirements to reinforcing materials are defined and the examples of constructive designs for increasing the soil base supporting power are provided.